DERADIKALISASI DAN INTEGRASI NILAI-NILAI PLURALITAS DALAM KURIKULUM PESANTREN SALAFI HARAKI DI INDONESIA - Mukhibat Mukhibat (IAIN Ponorogo, 2014)
Abstract: The beginning of twenty first century marks the proliferation of salafi-haraki Islamic boarding schools (pesantren) that blatantly reveals their distinctive thoughts, ideology and movement. These pesantrens advance puritan and literal-textual-fundamental understandings of Islam that potentially endanger the unity of Indonesia as a plural nation-state. The government must not only review the contents, materials and curriculum taught in radical pesantrens but also pay a close attention to their leaders’ and teachers’ methods and approaches to religious education both in class and beyond. This article offers strategies to develop Islamic school so it will not turn to be radical. This article argues that in order to preserve a very basic natural character of Indonesian pesantren, as a place to seed peace and tolerance, salfi-haraki pesantrens must integrate the values of multiculturalism and pluralism into their curriculum. This can be done by translating, assimilating and transforming work on pluralism. The values of pluralism will decimate the seeds of radicalism and fundamentalism and are transformed into agendas and activities, such as regular meeting, religious gathering and informal discussion as part of indirect teaching.